2001
DOI: 10.1002/mus.1194
|View full text |Cite
|
Sign up to set email alerts
|

A small dose of the immunosuppressive agent FK506 (tacrolimus) protects peripheral nerve from ischemic fiber degeneration

Abstract: The immunosuppressant agent FK506 (tacrolimus) has proven to be neuroprotective against brain ischemia, but there are no data on potential neuroprotective effects of FK506 in peripheral nerve ischemia. We examined the potential effects of two doses of FK506 in protecting peripheral nerve from ischemic fiber degeneration. Ischemia in the left sciatic nerve of the rat was produced by injecting 2 x 10(6) microspheres (14 microm) into the left femoral, hypogastric, and superior gluteal arteries in proportions of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 105 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…6 -17 The prototype immunophilin ligand FK506 has been shown to promote regeneration and functional recovery in in vivo animal models of peripheral nerve injury such as crush injury of sciatic and facial nerves. 8,11,13,24 We recently demonstrated that FK506 exerts potent neuroprotective effects on rat penile innervation and preserves erectile function in a cavernous nerve crush injury model. 18 In instances of sciatic and facial crush nerve injury, FKBP 12 localizations and upregulated expression have been confirmed and linked to nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…6 -17 The prototype immunophilin ligand FK506 has been shown to promote regeneration and functional recovery in in vivo animal models of peripheral nerve injury such as crush injury of sciatic and facial nerves. 8,11,13,24 We recently demonstrated that FK506 exerts potent neuroprotective effects on rat penile innervation and preserves erectile function in a cavernous nerve crush injury model. 18 In instances of sciatic and facial crush nerve injury, FKBP 12 localizations and upregulated expression have been confirmed and linked to nerve regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, the ability to manipulate nerve biology at the cellular level provides a significant improvement in nerve recovery [2,5]. In the last decade, some substances such as tacrolimus, an immunosuppressive agent, and alpha-lipoic acid have been shown to protect peripheral nerve from ischemic degeneration [6,7]. However, controversy still exists regarding peripheral nerve injuries with potentially devastating results at the moment.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Diabetes mellitus, vascular occlusive diseases, compression injuries, entrapments, tourniquet-induced peripheral nerve injuries, necrotizing vasculitis, and trauma are only a few of the pathological conditions that result in neuropathy associated with peripheral nerve ischemia. [ 17 28 ] The extent and type of damage to the nerve fiber depends on the duration of ischemia and blood flow amount. Furthermore, decompression and restoration of an adequate blood supply to peripheral nerves may predispose the nerves to reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%